ANALISIS PENDAPAT SISWA TERHADAP PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN GEOGEBRA PADA MATERI GARIS DAN SUDUT - Febriani Dicahya Fitri; Eka Senjayawati; Ratni Purwasih (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study aims to analyze students opinions on the line and angle material using a Contextual Teaching and Learning (CTL) approach with the help of geogebra applications. The research method used is descriptive qualitative research. The subjects of this study were 4 students of class VII in Batujajar. The instrument used is the scale of students' opinions on Contextual Teaching and Learning (CTL) learning with the help of the geogebra application. The student opinion scale consists of 10 statements containing 5 positive statements and 5 negative statements, the student opinion scale is used to determine the responses of respondents to Contextual Teaching and Learning (CTL) learning assisted by geogebra applications. The analysis of this study shows a positive response, namely almost all students think that students become more enthusiastic and learning becomes more fun, and almost all students also think that they have no difficulty in learning Contextual Teaching and Learning (CTL) or in using geogebra on line material and angle.